Substance Use, Military Experience, and Posttraumatic Stress Disorder among Veterans in Community-Based Residential Treatment. (3rd July 2019) - Yu, Jiang; Hussain, Shazia; Appel, Phil; Astone-Twerell, Janetta; Kearse, Roy; Harris, Brett
Abstract: This study examines the extent to which alcohol and drug use before military services is associated with post-service alcohol and drug use and symptoms of posttraumatic stress disorder (PTSD) among veterans in residential treatment. Face-to-face interviews were conducted with veterans in a major residential treatment center in New York City; 121 veteran patients participated in the study, with a 4% refusal rate. Premilitary service alcohol use tends to associate only with post-service alcohol use and preservice drug use only with postservice drug use; postservice use of alcohol is more closely correlated with PTSD symptoms than the use of drugs. Findings suggest that military culture of alcohol use should be taken into consideration when examining substance use and PTSD conditions among veterans and be included as part of the substance use disorder assessment.